(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article some aspects of the theory of the world state and the right are considered. The author’s position about the basic provisions making structure and contents of the theory of the world state and the right is stated. Methods of the argument of the theory of the world state are analysed. It is noted that the theory of the world state and the right was developed as it is represented, without the due consideration and many other factors difficult compatible or not compatible to process of global state and legal construction. Key words: theories of the world state and right, contradictory perception of idea of world association, sovereignty, contradictions.